Lithium tetrafluoroborate catalyzed highly efficient inter- and intramolecular aza-Michael addition with aromatic amines - Lad, Uday P.; Kulkarni, M. A.; Desai, Uday V.; Wadgaonkar, P. P. (Comptes Rendus Chimie, 2011)
Lithium tetrafluoroborate has been demonstrated for the first time to be an efficient catalyst in intermolecular aza-Michael addition aromatic amines to electron deficient alkenes. Suitability of the same catalyst in intramolecular aza-Michael addition leading 2-aryl-2,3-dihydroquinolin-4(1H) ones has also been described. (C) 2011 Published by Elsevier Masson SAS on behalf of Academie des sciences.
Keywords: 2-aryl-2; 3-dihydroquinolin-(4H)-1-ones; Anilines; Lithium tetrafluoroborate; Michael addition